Muscle involvement in Schönlein-Henoch syndrome. Issue 11 (November 1983) - Somekh, E; Fried, D; Hanukoglu, A
Abstract : Three patients with Schönlein-Henoch syndrome developed severe muscle pain in the legs. The pain, so severe that they were bedridden, subsided within a few days and was caused, we believe, by bleeding into the leg muscles.